Locus of control, hyperbolic preferences, and demand for commitment and savings: Evidence from rural Ethiopia - Abay, Kibrom A.; Berhane, Guush; Assefa, Thomas (2017)
We investigate the implications of individuals’ locus of control on time preferences in general and hyperbolic preferences in particular. We also investigate the implications of locus of control and hyperbolic preferences on demand for commitment and savings. The empirical analysis is based on a series of hypothetical time preference questions and choice exercises conducted on Ethiopian rural farmers. We find that locus of control significantly predicts discounting behavior in general and hyperbolic preferences in particular. We particularly find that individuals with an external locus of control are more likely to discount future payoffs hyperbolically. We further show that locus of control and hyperbolic preferences significantly predict demand for commitment devices and savings behavior. We find that those individuals with an external locus of control and those discounting future payoffs hyperbolically exhibit a higher demand for commitment device. These results provide interesting insights that may help in designing poverty reduction policies.